Current Scenario of Rape Cases Reported in Healthcare Teaching Hospital in the North East India - Dev Ashis Ramu Damu; Thoidingjam Bijoy Singh; Huidrom Nabachandra Singh (National Board of Examinations Journal of Medical Sciences)
Background: This study was done in Department of Forensic Medicine, RIMS, Imphal from July 2016 to June 2018. Objectives: To study trends of rape cases, identifying vulnerable survivors and common offenders and to identify injuries on survivors. Methods: Data were collected from cases of medicolegal examination of rape accused & survivor. Cases with no preceding or succeeding FIR, non-consenting cases were study were excluded. Demographic profile, month of the year, and victim-accused relations were noted. Results: In 352 cases, 185 were rape survivors & 167 were rape accused. 5.4% had a history of alcohol use by the accused and there is a positive co-relation between alcohol intake and injuries sustained by the survivor. Spermatozoa were detected in 18.56% on microscopic examination but were absent in 81.44%. Acid phosphatase present in 17.3% and absent in 82.7%. Conclusion: Sexual offence continues to be a prevalent but often overlooked menace to the society. Because of late reporting of sexual assault cases, medicolegal examination was done late. The reason behind late reporting is that the victim’s family and the accused family usually tries to solve or come to a consensus for the issue using customary laws among various ethnic communities and the help of police and law is taken only after they cannot come to an agreement. General bodily and private parts injuries found were associated with alcohol use by the accused. Majority of the sexual assault survivors were students followed by selfemployed workers.